Theories of Modern Art : a Source Book by Artists and Critics - Chipp, Herschel, B.; Argan, Giulio Carlo; Arp, Hans, Jean; Aurier, G.-Albert; Bacon, Francis; Baizerman, Saul; Baziotes, William; Beckmann, Max; Boccioni, Umberto; Boriani, Davide; Brancusi, Constantin; Braque, Georges; et al. (Berkeley / Los Angeles / London : University of California Press, 1968)
Arp, Hans (Jean) ; Aurenche, Louis ; Aurier, G.-Albert ; Bacon, Francis ; Baizerman, Saul ; Ball, Hugo ; Balla, Giacomo ; Baziotes, William ; Beckmann, Max ; Bell, Leland ; Bernard, Emile ; Blake, William ; Blanc, Charles ; Boccioni, Umberto ; Boriani, Davide ; Bouguereau, William Adolphe ; Bourdelle, Antoine ; Brancusi, Constantin ; Braque, Georges ; Breton, André ; Brisset, Jean-Pierre ; Cahill, Holger ; Calder, Alexander ; Camoin, Charles ; Carrà, Carlo ; Cézanne, Paul ; Chagall, Marc ; De Chirico, Giorgio ; Constant ; Cosimo, Piero Di ; Courbet, Gustave ; Croce, Benedetto ; Dali, Salvador ; Davis, Stuart ; Delacroix, Eugène ; Delaunay, Robert ; Denis, Maurice ; Derain, André ; van Doesburg, Theo ; Dondero, George A. ; Dubuffet, Jean ; Duchamp, Marcel ; Duchamp-Villon, Raymond ; Ensor, James ; Ernst, Max ; Ferber, Herbert ; Finkelstein, Louis ; Frank, Mary ; Gabo, Naum ; Gallatin, A.E. ; Gasquet, Joachim ; Gaudi, Antoni ; Gauguin, Paul ; Geist, Sidney ; Giacometti, Alberto ; Gleizes, Albert ; Goebbels, Joseph ; Van Gogh, Theo ; van Gogh, Vincent ; Van Gogh, Wilhelmina ; Gorky, Arshile ; Gottlieb, Adolph ; de Gourmont, Remy ; Greenberg, Clement ; Gris, Juan ; Gropius, Walter ; Guggenheim, Peggy ; Hajdu, Etienne ; Hartley, Marsden ; Henri, Robert ; Henry, Charles ; Hildebrand, Adolph von ; Höch, Hannah ; Hodler, Ferdinand ; Hoelzel, Adolf ; Hofmann, Hans ; Huelsenbeck, Richard ; Hugo, Valentine ; Huysmans, Joris-Karl ; Itten, Johannes ; Jaeger, Hans ; Janco, Marcel ; Jarry, Alfred ; Jewell, Edward Alden ; Kahn, Gustave ; Kahnweiler, Daniel-Henry ; Kandinsky, Wassily ; Kant, Immanuel ; Kaprow, Allan ; Kemenov, Vladimir ; Khrushchev, Nikita ; King, Phillip ; Kirchner, Ernst Ludwig ; Klee, Paul ; Kokoschka, Oskar ; de Kooning, Willem ; Kramer, Jilton ; etc.
Engels
boek